Teachers’ Limited Wait-Time Practice and Learners’ Participation opportunities in EFL Classroom Interaction - Bager Yaqubi; Mostafa Pourhaji Rokni (Journal of English Language Teaching and Learning, 2013)
Pairing theory with methodology, this study demonstrates how EFL teachers’ limited wait-time practice structures in and affects the structuring of the unfolding classroom discourse with reference to learners’ participation opportunities. Informed by the tenets of conversation analysis, we have observed, videotaped, and transcribed line-by-line 10 EFL teachers’ naturally-occurring classroom interaction. Analyses of six episodes from the data suggest that teachers’ seemingly inadvertent implementation of limited wait-time tends to reduce learners’ interactional space. Moreover, it serves the (dys)function of triggering those interactive practices whose structuring diverts teacher talk from the major pedagogic goal, i.e. increasing leaner participation. The findings of this study can be analytically generalized to the theoretical model of communicative competence. They can also help teachers on their way towards developing their classroom interactional competence.